Análise da qualidade microbiológica e sujidades em melado de cana-de-açúcar - Belé, Jhéssica Samara Abreu Holsbach Silva (Universidade Federal de São Carlos, 2019)
Sugarcane syrup is defined as the product obtained by the concentration of sugarcane juice (Saccharum officinarum L.) or from melted sugarcane. The sugar cane syrup have good acceptance in the Brazilian market and can be used as a sweetener replacing refined sugar, besides containing important minerals. However, the existing specific standards are insufficient to accurately assess the quality of this product. In this context, 15 commercial brands of sugarcane syrup were analyzed based on microbiological properties, moisture, water activity and foreign matter. All brands showed absence of total coliforms and Escherichia coli, while five brands showed contamination by mesophilic bacteria, molds and yeasts. In relation to the count of thermophilic bacteria flat-sour three marks showed contamination, however within the maximum allowed by the legislations. Humidity ranged from 9 to 26.1%, indicating that there was no standardization among the samples analyzed. In relation to water activity, the results ranged from 0.63 to 0.74. The analysis matter strange, conducted under light transmission microscopy, revealed that 14 (93%) brands contained some kind of foreign material, with only one brand (M) meeting the standards. The current national standard (RDC nº. 12/2001) does not contain enough information to analyze the quality of syrup, so an update is necessary to ensure that this product has a quality standard and can be consumed safely.
Analysis of microbiological quality and filth in sugarcane syrup
Keywords: Alimento; Melado; Food; Sugarcane syrup; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS